2013
DOI: 10.5539/jas.v5n4p112
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Land Use Systems on Selected Physico-Chemical Properties of Soils in Northwestern Ethiopia

Abstract: Information about effects of different land use systems on soil physico-chemical properties is crucial for best land management practices. This study was, therefore, conducted to evaluate the same on Nitosols of Achefer District, Northwestern Ethiopia. The landuse systems studied included grassland, cultivated land, plantation forest and natural forest. The research was superimposed on land use systems that were located nearby on similar soil, contour line and slope classes. Undisturbed core and disturbed comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
33
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 20 publications
15
33
1
Order By: Relevance
“…Our results are thus consistent with previous studies that reported higher bulk densities for pastures or croplands compared to native or forest plantations in Argentina (Cisneros et al, 1999), the north-eastern USA (Zhou et al, 2008), Costa Rica (Reiners et al, 1994), Iraq (Emadi et al, 2008) and Ethiopia (Selassie and Ayanna, 2013).…”
Section: Discussionsupporting
confidence: 93%
“…Our results are thus consistent with previous studies that reported higher bulk densities for pastures or croplands compared to native or forest plantations in Argentina (Cisneros et al, 1999), the north-eastern USA (Zhou et al, 2008), Costa Rica (Reiners et al, 1994), Iraq (Emadi et al, 2008) and Ethiopia (Selassie and Ayanna, 2013).…”
Section: Discussionsupporting
confidence: 93%
“…This is probably attributed to short rotation age of E. globulus (4 years). These findings are in agreement with similar study report by Selassie and Ayanna (2013), Getachew et al (2012) and Haile et al (2014) who had reported no significant difference on the same between E. globulus and cultivated land.…”
Section: Soil Physical Propertiessupporting
confidence: 93%
“…The finding agrees with Haile et al (2014) who had reported lower pH value under Eucalyptus woodlots compared to other land use types. However, the pH value (5.55) of this study is greater than that previous report by Selassie and Ayanna (2013) who reported pH values of 5.06 and 5.01 under the E. globulus at Abechikeli Mariam and Aferfida Georgis sites, respectively. Duguma et al (2010) also reported a lower pH value (5.06) under E. globulus compared to homestead, croplands and grazing lands at central highlands of Ethiopia.…”
Section: Soil Chemical Propertiescontrasting
confidence: 88%
“…Our result is in line with the findings of different authors; Lalisa et al (2010) and Yihenew and Getachew (2013) reported that in Ethiopian central highlands that soil pH is lower in wood lots/eucalyptus plantation as compared to homestead, croplands and grazing lands. Zerfu (2002) also noted that eucalyptus globulus plantation sites showed high level of active acidity or low pH as compared to agricultural lands.…”
Section: Soil Chemical Propertiessupporting
confidence: 93%
“…Again Tilashwork et al (2012) also found that in Koga irrigation watershed, soils bulk densities at all depths and distances from Eucalyptus camaldulensis and Croton macrostachyus stands are low and ranged from 1.0 to 1.1 g cm -3 . The lower bulk density in crop lands as compared to eucalyptus plantation also reported by (Yihenew & Getachew, 2013). The lower bulk density under eucalyptus may be due to organic matter accumulation and les trampling by livestock.…”
Section: Soil Physical Propertiesmentioning
confidence: 49%